Sequentially amplified circularly polarized ultraviolet luminescence for enantioselective photopolymerization - Han, Dongxue (Nat Commun, 2020)
Chiral optical materials based on circularly polarized luminescence (CPL) have emerged rapidly due to their feasible applications in diverse fields of research. However, limited to the small luminescence dissymmetry factor (g(lum)), real application examples have rarely been reported. Here, we present a complex system, which show intense circularly polarized ultraviolet luminescence (CPUVL) with large g(lum) value, enabling a chiral UV light triggered enantioselective polymerization. By integrating sensitized triplet-triplet annihilation upconversion and CPL, both visible-to-UV upconversion emission and upconverted circularly polarized ultraviolet luminescence (UC-CPUVL) were obtained in the systems, built of chiral annihilator R(S)-4,12-biphenyl[2,2]paracyclophane (R-/S-TP), and a thermally activated delayed fluorescence (TADF) sensitizer. After dispersing this upconversion system into room-temperature nematic liquid crystal, induced chiral nematic liquid crystal could significantly amplify the g(lum) value (0.19) of UC-CPUVL. Further, the UC-CPUVL emission has been used to trigger the enantioselective photopolymerization of diacetylene. This work paves the way for the further development of functional application of CPL active materials.